2003
DOI: 10.1002/bem.10097
|View full text |Cite
|
Sign up to set email alerts
|

No influence of magnetic fields on cell cycle progression using conditions relevant for patients during MRI

Abstract: The purpose of this study was to examine whether exposure to magnetic fields (MFs) relevant for magnetic resonance imaging (MRI) in clinical routine influences cell cycle progression in two tumor cell lines in vitro. HL60 and EA2 cells were exposed to four types of MFs: (i) static MF of 1.5 and 7.05 T, (ii) extremely low frequency magnetic gradient fields (ELFMGFs) with +/- 10 mT/m and 100 Hz, as well as +/- 100 mT/m and 100 Hz, (iii) pulsed high frequency MF in the radiofrequency (RF) range (63.6 MHz, 5.8 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…There may be concern that a high magnetic field can cause damage to the human body; however, reports indicated that static EMF from 0.3 T up to 1 T for more than 8 h/day did not have deleterious effects (25,(27)(28)(29). Even though the World Health Organization is concerned about the in vivo and in vitro effects of high EMF of more than 1 T, there is no definite evidence that high EMF will lead to damage in vivo and in vitro (30,31). Schiffer et al (30) reported that no detectable side effects of magnetic fields (static magnetic fields ranging from 1.5 to 7.05 T and exposure periods ranging from 1 to 24 h) were observed in cell cycle progression in HL60 cells and EA2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be concern that a high magnetic field can cause damage to the human body; however, reports indicated that static EMF from 0.3 T up to 1 T for more than 8 h/day did not have deleterious effects (25,(27)(28)(29). Even though the World Health Organization is concerned about the in vivo and in vitro effects of high EMF of more than 1 T, there is no definite evidence that high EMF will lead to damage in vivo and in vitro (30,31). Schiffer et al (30) reported that no detectable side effects of magnetic fields (static magnetic fields ranging from 1.5 to 7.05 T and exposure periods ranging from 1 to 24 h) were observed in cell cycle progression in HL60 cells and EA2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the World Health Organization is concerned about the in vivo and in vitro effects of high EMF of more than 1 T, there is no definite evidence that high EMF will lead to damage in vivo and in vitro (30,31). Schiffer et al (30) reported that no detectable side effects of magnetic fields (static magnetic fields ranging from 1.5 to 7.05 T and exposure periods ranging from 1 to 24 h) were observed in cell cycle progression in HL60 cells and EA2 cells. The formula for our innovative SPEMF is below the intensity and time of the above-mentioned for inducing chondrogenesis of ADSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tumor cell lines exposed to a 7.05 T SMF and a time-varying field showed no alterations of cell cycle progression [Schiffer et al, 2003]. Additionally, a study by Schwenzer et al [2007a] using human embryonic lung fibroblasts found no effects on cell proliferation, cell division, or gene expression after exposure to a 3 T SMF and a RF field.…”
Section: Introductionmentioning
confidence: 98%
“…However, mixed experimental reports from the laboratories are in the literature, which seem to be controversial. Some studies show that SMFs in this range do not affect cell growth or cell cycle [9, 10], while the others show that they may have some beneficial effects on cancer growth inhibition, either alone or in combination with chemodrugs or radiation [1114]. Therefore, the exact effects, especially prolonged exposure of SMFs in the range of MRI machines on human bodies are still inconclusive.…”
Section: Introductionmentioning
confidence: 99%